Uji Aktivitas Antidiare Ekstrak Etanol Daun Kelor (Moringa Oleifera Lam.) Terhadap Mencit Putih Jantan (Mus Musculus) Yang Diinduksi Oleum Ricini - Rifda Naufa Lina; Hasty Martha Wijaya; Annis Rahmawaty; Jamiyah Nur Rohmah (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2024)
Diarrhea is a condition in which a person defecates with a soft or runny consistency, it can even be water alone and the frequency is more frequent (usually three or more times) in one day. One of the beneficial plants is the Moringa oleifera Lam. Plant. Flavonoids, tannins and steroids in Moringa leaves are thought to be anti-diarrhea. This study aims to determine the antidiarrheal activity of the ethanol extract of Moringa oleifera Lam. Leaves against male white mice (Mus musculus) induced by Oleum ricini. Observations were made for 3 hours. This research is an experimental study divided into 6 groups, namely the normal group, positive control (Loperamid HCl), negative control (Na CMC), and ethanol extract of moringa leaves at a dose of 200 mg / KgBB, 400 Mg / KgBB and 800 mg / KgBB. Numeric data were processed using SPSS with One Way ANOVA test. The results showed that the optimal dose was 200 mg / KgBW in the ethanol extract of Moringa oleifera Lam. Leaves as an antidiarrheal in male white mice (Mus musculus) induced by Oleum ricini.